Characteristics of Seismic Waves Produced by Surface Mining Operations - Tom Goforth; Rongmao Zhou (International Society of Explosives Engineers, 2006)
The interest of seismologists in mining explosions has increased substantially with the construction of the International Monitoring System (IMS). The IMS supports the Comprehensive Nuclear Test-Ban Treaty by providing global data coverage from seismic, hydro acoustic, infrasonic, and radionuclide sensors that will detect a host of natural and man-made events at regional (<2000 km) distances. Ideally, the recorded data can be used to identify those events that have explosive characteristics and therefore might be clandestine nuclear tests. The regional observations assure the detection of mining explosions, and these must be properly identified to avoid false alarms of the monitoring system. Cooperation with the mining industry, including documentation of the firing programs, provides critical information necessary to characterize the seismograms.